(untitled) (Colombia Medica, 2007)
The anterior, middle and the posterior clinoid processes are located in the middle cranial fossa of the skull. The posterior boundary of the pituitary fossa is formed by the dorsum sellae, the supero-lateral angles of which are raised to form the posterior clinoid process. Unlike the anterior clinoid process, the posterior clinoid process has received less attention in past research studies. The anatomy textbooks do not mention about the anomalies pertaining to the posterior clinoid process and the main source of information are the research reports. The present osteological study describes anomalous posterior clinoid process, detected in two human skulls, during routine undergraduate medical teaching and also discusses its clinical importance. The posterior clinoid process anomalies may be responsible for the altered arrangement of the tentorium cerebelli which is attached to it. The internal carotid artery is often explored by the neuro-surgeon and any bony abnormalities in its vicinity, would result in a difficult situation, while performing clinoidectomy operations. Anomalous posterior clinoid process, may compress the internal carotid artery. The close position of the superior petrosal sinus and the internal carotid artery to the posterior clinoid process, makes it vulnerable to injuries and thus it is important for the neuro-surgeons performing clinoidectomy operations. The anatomy of the posterior clinoid process may be important for neuro surgeons and radiologists in day to day clinical practice.